Heterogeneous spectrum of CFTR gene mutations in Chinese patients with CAVD and the dilemma of genetic blocking strategy. Issue 3 (14th July 2022) - Feng, Jiarong; Zhang, Yanan; Yang, Xiaojian; Zhang, Yan
Abstract : In brief: The genetic heterogeneity of CFTR gene mutations in Chinese patients with congenital absence of the vas deferens (CAVD) differs from the hotspot mutation pattern in Caucasians. This paper reviews and suggests a more suitable screening strategy for the Chinese considering the dilemma of CFTR genetic blocking. Abstract: Congenital absence of the vas deferens (CAVD) is a major cause of obstructive azoospermia and male infertility, with CFTR gene mutation as the main pathogenesis. Other genes such as ADGRG2, SLC9A3, and PANK2 have been discovered and proven to be associated with CAVD in recent studies. Multiple CFTR hotspot mutations have been found in Caucasians in several foreign countries, and relevant genetic counseling and preimplantation genetic diagnosis (PGD) have been conducted for decades. However, when we examined research on Chinese CAVD, we discovered that CFTR mutations show heterogeneity in the Chinese Han population, and there is currently no well-established screening strategy. Therefore, we have reviewed the literature, combining domestic and international research as well as our own, aiming to review research progress on the CFTR gene in China and discuss the appropriate scope for CFTR gene detection, the detection efficiency of other CAVD-related genes, and the screening strategy applicable to the Chinese Han population. This study provides more valuable information for genetic counseling and a theoretical basis for PGD and treatment for couples with CAVD when seeking reproductive assistance.